A European news site for financial and geopolitical analysis - Foundation, GEFIRA (GEFIRA, 2017)
The Western globalist elites have not digested Trump's victory or Brexit yet. They are having a hard time dealing with their ideological failures, and when the reality dares not to comply with their day dreaming, they go online and create a parallel world, where their expert predictions always tur...